Local de produção, armazenamento e qualidade de sementes de soja - Sanches, Maurício Feis Ganz [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The soybean is produced across the country, however, environmental and phytosanitary factors may limit the obtaining of seed of physiological and sanitary quality satisfactory. Thus, the present study aimed to evaluate the physiological, sanitary and chemical quality, initial and during the storage of soybean seeds cultivars harvested at production sites with different soil and climatic characteristics and verify the influence of genotype-environment relationship. It was used seeds of two soybean cultivars early cycle (M-SOY 7908 RR and CD 2630 RR) from four regions with different edaphoclimatic characteristics. Seeds were evaluated by germination, vigor (accelerated aging, electrical conductivity and tetrazolium), sodium hypochlorite, sanity, determination of oil content and seedling emergence in the field tests. After determining the initial seed quality, seeds were stored in a dry chamber (20 ± 2 °C and 45% RH of air) and evaluated again after six and 12 months. It was observed to MSOY 7908 RR cultivar that the region of Perdizes (altitude 1,030 m) was favorable for production of seeds with high physiological, chemical and sanitary quality when compared to those from Casa Branca (altitude 600 m), due to milder weather conditions verified in the first city. Regarding the CD 2630 RR cultivar, seeds produced in Altinópolis (altitude 980 m) had lower physiological, chemical and sanitary quality when compared to those from Sales Oliveira (region with lower altitude), differing from results found in the literature. This behavior was due to the high precipitation and temperature verified during the pre-harvest, causing moisture damage harmful to performance. In both cultivars and four production sites studied, there was reduction of the physiological and chemical quality during storage. Furthermore, the pathogens initially present in the seeds also showed decline as its incidence. Thus, seeds with high physiological, chemical and ...

A soja é produzida em todo o país, entretanto, fatores ambientais e fitossanitários podem limitar a obtenção de sementes de qualidade fisiológica e sanitária satisfatórias. Assim, a presente pesquisa teve como objetivo avaliar a qualidade fisiológica, sanitária e química inicial e durante o armazenamento de sementes de cultivares de soja colhidos em locais de produção com características edafoclimáticas distintas e verificar a influência da relação genótipo-ambiente. Foram utilizadas sementes de dois cultivares de soja de ciclo precoce (MSOY 7908 RR e CD 2630 RR) provenientes de quatro regiões com características edafoclimáticas distintas. As sementes foram avaliadas pelos testes de germinação, vigor (envelhecimento acelerado, condutividade elétrica e tetrazólio), hipoclorito de sódio, sanidade, determinação do teor de óleo e emergência de plântulas em campo. Após a determinação da qualidade inicial, as sementes foram armazenadas em câmara seca (20 ± 2 °C e 45% UR do ar) e avaliadas após seis e 12 meses. Observou-se para o cultivar MSOY 7908 RR, que a região de Perdizes (altitude de 1.030 m) foi favorável à produção de sementes de melhor qualidade fisiológica, química e sanitária quando comparadas às provenientes de Casa Branca (altitude de 600 m), devido às condições climáticas mais amenas. Com relação ao cultivar CD 2630 RR, sementes produzidas em Altinópolis (altitude de 980 m) tiveram menor qualidade fisiológica, química e sanitária quando comparadas às provenientes de Sales Oliveira, região de menor altitude, diferindo do encontrado na literatura. Esse comportamento deveu-se à precipitação e temperatura elevadas durante a pré-colheita que ocasionaram danos por umidade prejudiciais ao desempenho das sementes. Para ambos os cultivares e nos quatro locais de produção estudados, houve redução da qualidade fisiológica e química durante o período de armazenamento. Além disso...
Keywords: Soja; Sementes; Soja - Qualidade; Fisiologia vegetal; Influencia do clima; Seeds